Drama 7-11 : developing primary teaching skills - Kitson, Neil.; Spiby, Ian. (London : Routledge, 2015)
This book is a practical guide to teaching drama and provides a clear and coherent framework together with a theoretical underpinning which will allow teachers to create their own drama lessons from an informed standpoint.
Includes bibliographical references (p. [109]-110) and index.
Keywords: Drama -- Study and teaching (Primary).; Acting teachers -- Training of